2016
DOI: 10.1371/journal.pone.0167330
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Lipase and Lipoxygenase of Wheat Germ with Temperature-Controlled Short Wave Infrared Radiation and Its Effect on Storage Stability and Quality of Wheat Germ Oil

Abstract: Wheat germ (WG) is quite susceptible to deterioration due to the presence of lipase (LA) and lipoxygenase (LOX). Therefore it is indispensable to adopt a stabilization step to decrease the activity of LA and LOX while retaining a maximum level of nutrients. But over-drying can make foodstuffs more susceptible to autoxidation. So a stabilization protocol for inactivating LA and LOX of WG with a temperature- controlled short wave infrared (SIR) radiation system was adopted to retard its rancidity and retain a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…This in turn reduces the oil extraction time and solvent and energy consumption. In addition, blanching cleans the seeds, inactivates the lipid oxidation enzymes, increases mass transport in the plant tissue and considerably reduces seed drying time [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…This in turn reduces the oil extraction time and solvent and energy consumption. In addition, blanching cleans the seeds, inactivates the lipid oxidation enzymes, increases mass transport in the plant tissue and considerably reduces seed drying time [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to develop the suitable methods for WG stabilization, including short wave infrared radiation [3], gamma irradiation [4], roasting [5][6][7], steaming [8,9], microwave treatment [9][10][11][12], toasting [13,14], temperature controlled water-bath [11,12], sourdough fermentation [14], and fluidization method [9,[15][16][17][18]. However, the processing temperature of these methods was high.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that all the treatments had no significant influence ( p > .05) on the fatty acid composition. Similar findings were reported by Yılmaz, Tuncel, and Kocabıyık () Maria (Irakli et al, ) and Li et al () for infrared radiation heating. And Loypimai indicated that both steaming and ohmic heating had no significant influence ( p > .05) on the fatty acid composition of rice bran oil (Loypimai, Moongngarm, & Chottanom, ).…”
Section: Resultsmentioning
confidence: 99%